2017
DOI: 10.2106/jbjs.17.00341
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular Global Insufficiency in Patients with Down Syndrome and Hip-Related Symptoms

Abstract: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…4 A recent tomographic study using reformatted images through the anatomical axis of the femoral neck, showed no difference in the neck-shaft angle between patients with Down syndrome and matched-control individuals. 16 Recent evidence suggested that the acetabulum is retroverted in Down syndrome, leading to an insufficient posterior support to the femoral head. 9 , 12 , 16 One study described the posterior acetabular wall as deficient and aggravating the retroversion of the acetabulum, leading to further posterior hip instability.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…4 A recent tomographic study using reformatted images through the anatomical axis of the femoral neck, showed no difference in the neck-shaft angle between patients with Down syndrome and matched-control individuals. 16 Recent evidence suggested that the acetabulum is retroverted in Down syndrome, leading to an insufficient posterior support to the femoral head. 9 , 12 , 16 One study described the posterior acetabular wall as deficient and aggravating the retroversion of the acetabulum, leading to further posterior hip instability.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Recent evidence suggested that the acetabulum is retroverted in Down syndrome, leading to an insufficient posterior support to the femoral head. 9 , 12 , 16 One study described the posterior acetabular wall as deficient and aggravating the retroversion of the acetabulum, leading to further posterior hip instability. 14 A recent study reported a global insufficiency of the acetabulum in patients with Down syndrome and hip symptoms, and that the acetabulum is more retroverted and shallower compared with healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations